ANALISIS LAJU INFILTRASI PADA TEGAKAN PINUS, MAHONI, AKASIA DAN MERSAWA DI KOTA BANJARBARU - Mujari Rahman; Syarifuddin Kadir; Badaruddin Badaruddin (Universitas Lambung Mangkurat, 2022)
Knowing the rate of infiltration in the stands of Pinus, Mahogany, Acacia and Mersawa in Banjarbaru City, Analyzing the magnitude of infiltration capacity in the stands of Pinus, Mahogany, Acacia and Mersawa.In this study there is data retrieval and data collection, in the collection of infiltration data conducted under the stands of Pinus, Mahogany, Acacia, and Mersawa in Banjarbaru.Measurement of infiltration rate is performed 3 times on each stand Pinus, Mahogany, Acacia and Mersawa.In data collection there are two methods, namely primary data and secondary data, primary data is done directly in the field using an infiltrometer tool placed on a predetermined sample location.The required secondary data is supporting data such as location maps.In this study, the largest average infiltration rate was found in acacia stands with a value of 3.67 mm/h and the lowest at mersawa stands with a value of 1.50 mm/h.While the average capacity and volume of infiltration is the largest in acacia stands with an average capacity value of 3,589 mm /h and a volume of 1,519 mm3, while the lowest infiltration capacity and volume is in the pine stand with a value of 1,570 mm / h and the lowest volume of 0.800 mm3.Mengetahui laju infiltrasi pada tegakan Pinus, Mahoni, Akasia dan Mersawa di Kota Banjarbaru, Menganalisis besarnya kapasitas infiltrasi pada tegakan Pinus, Mahoni, Akasia dan Mersawa. Penelitian ini terdapat pengambilan data dan pengumpulan data, pada pengambilan data infiltrasi dilakukan dibawah tegakan Pinus, Mahoni, Akasia, dan Mersawa di Banjarbaru. Pengukuran laju infiltrasi dilakukan dalam 3 kali ulangan pada setiap tegakan Pinus, Mahoni, Akasia dan Mersawa. Dalam pengumpulan data terdapat dua metode yaitu data primer dan data skunder, data primer dilakukan langsung dilapangan dengan menggunakan alat infiltrometer yang diletakan pada lokasi sampel yang sudah ditentukan. Data skunder yang diperlukan ialah data penunjang seperti peta lokasi. Dalam penelitian ini rata-rata laju infiltrasi terbesar terdapat pada tegakan akasia dengan nilai 3,67 mm/jam dan yang terendah pada tegakan mersawa dengan nilai 1,50 mm/jam. Sedangkan rata-rata kapasitas dan volume infiltrasi terbesar pada tegakan akasia dengan nilai rata-rata kapasitas 3,589 mm/jam dan volume 1,519 mm3, sedangkan kapasitas dan volume infiltrasi terendah ada pada tegakan pinus dengan nilai 1,570 mm/jam dan volume terendah 0,800 mm3.